Vanadium trioxide mediated peroxymonosulfate for fast metronidazole oxidation: Stepwise oxidation of vanadium for donating electrons - Jiao Shen; Feng Cheng; Yichi Chen; Li, Zeyu; Yang Liu; Yue Yuan; Peng Zhou; Liu, Wen; Bo Lai; Yongli Zhang (Separation and Purification Technology, 2022)
In this study, vanadium trioxide (V2O3) was adopted to activate PMS via a Fenton-like reaction to degrade metronidazole (MNZ). The V2O3-PMS system can almost completely degrade MNZ at 30 min with 42.4% TOC removal. Comparative tests reveal that V2O3 stands out among a variety of heterogeneous catalysts, including metallic oxides and carbon materials. Sulfate radicals (SO4•−) and hydroxyl radicals (•OH) derived from PMS decomposition are major reactive oxygen species, based on quenching tests, electron spin resonance (ESR) analysis, the steady-state concentrations of radicals ([SO4•−]ss = 5.1 × 10-13 M and [•OH]ss = 4.0 × 10-14 M), and kinetics model. The process of stepwise electron transfer from vanadium species to PMS to produce reactive radicals was proved by small-molecule simulation experiments and pickling experiments of vanadium oxides. Possible pathways of MNZ degradation were proposed based on the results of LC-MS and Fukui function, including two stages of the hydroxylation and bond cleavage of nitro and the subsequent ring-opening. This study reveals the high reusability and practicability of the V2O3-PMS system over a relatively wide pH range, which puts forward a new vision on V2O3 induced Fenton-like reactions and a new reference method for the removal of medical organic contaminants in water.
Keywords: Metronidazole; Peroxymonosulfate; Steady-state model; Sulfate radical; Vanadium trioxide